2007
DOI: 10.1007/s00253-007-1138-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of calcium ion on the biodegradation of octylphenol polyethoxylates, and the antiandrogenic activity of their biodegradates

Abstract: Because limes have been used as important fertilizers to neutralize acidified farmland in Japan, our interest in this study was focused on the effect of calcium ion on the biodegradation of octylphenol polyethoxylates (OPEOn) by a pure culture of Pseudomonas putida S5 isolated from a rice paddy field in Japan. In the presence of calcium ion, P. putida S5 accelerated the formation of octylphenol oligoethoxy carboxylates (OPECn) rather than that of octylphenol oligoethoxylates under an aerobic condition, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Because this compound is characterized with an average of 9.5 ethoxy segments per molecule, we calculated its molecular weight to be 624.32. Surfactants with shorter ethylene oxide chains and the carboxylic acid derivatives used as standards were synthesized and purified by the method described by Shibata et al 21) …”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because this compound is characterized with an average of 9.5 ethoxy segments per molecule, we calculated its molecular weight to be 624.32. Surfactants with shorter ethylene oxide chains and the carboxylic acid derivatives used as standards were synthesized and purified by the method described by Shibata et al 21) …”
Section: Reagentsmentioning
confidence: 99%
“…[17][18][19][20] Moreover, the biodegradation of APEO n is significantly dependent on environmental conditions. 21,22) Consequently, the well-characterized microbial degradation of APEO n highlights the importance of understanding and predicting microbial behavior for bioremediation or prevention of APEO n pollution. 17,20,21) Although it is difficult to confirm changes in microbial diversity caused by human activity without supporting data, we notice these changes whenever we are faced with their adverse effects.…”
mentioning
confidence: 99%
“…3,11) Moreover, this study revealed that APEO n was biodegraded into many type of degradation patterns by diverse bacteria in the environment, suggesting that a rapid and reliable bacterial identication method will be necessary to characterize the biodegradation mechanism of man-made chemicals, especially when resultant biodegradation compounds may have an environmental impact. e MALDI-TOF MS is currently used for the rapid and reliable identi cation of bacteria at the species level especially in clinical diagnostic microbiology.…”
Section: E S10-germs Methods For the Identi Cation Of Opeo N -Degradinmentioning
confidence: 99%
“…9,10) Moreover, environmental elements, such as Mg 2+ , Ca 2+ , and Fe 3+ , signi cantly in uence the nal degradation metabolites. 3,11) In a previous study, we demonstrated that bacteria that can degrade OPEO n to estrogenic and antiandrogenic metabolites are ubiquitous in paddy elds in Japan. 12,13) Furthermore, the study of the dynamic relationship between the microbial diversity and biodegradation capacity of OPEO n using enrichment cultures of various sediments from Iwata River in Japan revealed that OPEO n -degrading bacteria are widely distributed at the sites of di erent types of human activity along Iwata River.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation